A Paradigmatic Model for the Expansion of Riḍawī Literature for Children and Adolescents in Textbooks and Schools - Tayebeh Zareie (پژوهش در آموزش معارف و تربیت اسلامی)
Riḍawī literature for children and adolescents, as a branch of literary studies, plays a pivotal role in the education and socialization of the youth. However, it appears to be underrepresented in textbooks and school curricula. Understanding the conditions, causes, and influencing factors for its expansion can facilitate the attainment of various educational dimensions and the ideal of perfection in this process. Accordingly, the present study aims to propose a paradigmatic model for the proliferation of Riḍawī literature for children and adolescents within textbooks and educational institutions. The research adopts a qualitative methodology grounded in the grounded theory approach. Data were collected through theoretical and purposive sampling via in-depth semi-structured interviews with university professors and teachers in Kermanshah Province. The data were then conceptualized and analyzed through three coding processes: open, axial, and selective coding. The research findings encompass 285 initial concepts, 104 sub-themes, and 17 main themes, culminating in the core category of "expansion of Riḍawī literature for children and adolescents in textbooks and schools." The resulting paradigmatic model delineates the necessary conditions, causes, factors, and imperatives. To achieve the desired outcomes, it is imperative to accord greater attention to the influencing components by adopting appropriate measures and strategies to enhance this process.